Pelatihan Peningkatan Kapasitas Petugas Kebersihan Hotel dan Restoran di Kabupaten Semarang - Alleta Dwi Maria; Azis Nur Rosyid; Wahyu Mafatikhul Aulia; Dyan Triana Putra (Lembaga Pengembangan Kinerja Dosen, 2025)
Capacity-building training for housekeeping staff in hotels and restaurants is a crucial aspect of maintaining service quality and enhancing customer satisfaction. Competent housekeeping personnel not only ensure physical cleanliness but also directly impact the reputation, image, and competitiveness of businesses in the hospitality and restaurant sectors. This community service program aims to develop the capacity of housekeeping staff through focused training on mastering cleaning techniques, effective waste management, and the proper and safe use of cleaning tools and materials. The training methodology is conducted directly using a participatory approach, allowing participants to actively engage in practical simulations, discussions, and case studies related to cleaning procedures, operational standards, and waste handling. Evaluation is conducted using pre-test and post-test assessments to measure improvements in participants’ knowledge, skills, and understanding of good cleaning practices. Results demonstrate significant improvements in mastering cleaning techniques, understanding waste management, and the ability to use cleaning tools and materials correctly. Additionally, participants reported increased awareness of the importance of consistently maintaining cleanliness standards, which is expected to be applied in daily workplace activities. The contribution of this community service provides tangible benefits in enhancing human resource quality in the hotel and restaurant sectors while supporting the achievement of professional, hygienic, and environmentally friendly service standards. This training is expected to serve as a sustainable model for the continuous development of housekeeping staff competencies in the broader hospitality and tourism industry.